STRATEGI SAVE THE CHILDREN DALAM MEMINIMALISIR BUDAYA KEKERASAN PENDIDIKAN ANAK USIA DINI DI KABUPATEN TIMOR TENGAH UTARA - Ronaldus Nurak (Program Studi Imu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Timor, 2022)
International non governmental organizations are important part of international relations dynamics. Limitations and authority from a country no longer discuss the concept of classical International Relations, is agreed about openness to globalization in the modern world. One of the concerns of INGO is the lives of children, especially children in areas that experience victims of injustice, experiencing disasters as well as other reasons which are very detrimental to the lives of children. Why should children be considered? Because children are the next generation of aspirations for the nation's struggle as well as human resources in the future. Departing from this idea, the main interests to grow and develop in a child's life must be given priority, because the age of children is a time when children should get good access in all things. However, not all children have the same opportunity to realize their hopes and aspirations. Many of them are at high risk to grow and develop healthily, get a good education, because of various obstacles that are experienced, both natural and also because of human problems themselves. Timor Tengah Utara Regency is one of the places where INGO Save The Children provides assistance for early childhood